Does It Matter Having Constructivist or Traditional Teaching Beliefs for Academic Achievement: A Study of Preservice Teachers - KARTAL, Büşra (International Dialogues on Education Journal, 2022)
The conceptions of teaching and learning influence the ways of teaching and learning, and naturally are associated with students’ motivation, self-efficacy, and achievement. Constructive teaching and learning conceptions provide a productive learning environment to train students equipped with 21st-century skills. Therefore, it is still crucial to examine preservice teachers’ conceptions. This study investigates preservice teachers’ conceptions of teaching and learning in terms of gender, grade level, and department and reveals the relationship between preservice teachers’ conceptions and academic performance. Data was collected from 513 preservice teachers by using “The Teaching and Learning Conceptions Questionnaire.” Results indicated that female preservice teachers have more constructive beliefs than males. First-grades had the most traditional beliefs than others. Besides, second and third-grade preservice teachers had more constructive beliefs than fourth grades. Regression analysis that was performed to reveal the relationship between conceptions and academic achievement showed that PSTs’ constructive conceptions increase their academic performance while traditional conceptions decrease.